How does climate change alter agricultural strategies to support food security? - Thornton, Philip K.; Lipper, Leslie (International Food Policy Research Institute, 2014)
The purpose of the paper is to identify how climate change affects how we should approach the process of transforming agricultural systems (including crops, livestock, fisheries and forestry) to support global food security and poverty reduction in a sustainable way. We also identify implications for FAO (Food and Agriculture Organization of the United Nations) and CGIAR priorities.